MANAJEMEN KURIKULUM INOVATIF DALAM MEWUJUDKAN PENDIDIKAN INKLUSIF: LITERATUR REVIEW - Rijal, Muh (Jurusan Pendidikan Luar Biasa, 2024)
This study is a systematic literature review that aims to identify innovative forms of curriculum management to support inclusive education for learners with special needs. Based on a literature review of ten articles published between 2018 and 2023, this research classifies inclusive curriculum management into four main categories: curriculum planning, curriculum organization, curriculum implementation and curriculum evaluation. Each category offers management strategies that can be adapted to create a learning environment that supports and embraces student diversity. The planning process includes modifying the curriculum to accommodate students' specific needs, while organizing focuses on collaboration among staff and effective utilization of resources. Implementation involves adaptive teaching methods that match students' individual abilities, and evaluation aims to assess success and make continuous improvements to the curriculum. The findings provide practical guidance for educational institutions in developing a more inclusive curriculum, which not only improves access to education but also quality and equity in learning.